2008
DOI: 10.1097/gme.0b013e318169332a
|View full text |Cite
|
Sign up to set email alerts
|

Black cohosh has central opioid activity in postmenopausal women

Abstract: Objective-To test whether black cohosh (BC) exhibits an action on the central endogenous opioid system in postmenopausal women.Design-A mechanistic study conducted in the same individuals of LH pulsatility with a saline/ naloxone (NAL) challenge (n=6) and PET imaging with [ 11 C]carfentanil, a selective μ-opioid receptor radioligand (n= 5), before and after 12 weeks of unblinded treatment with a popular black cohosh daily supplement.Results-Black cohosh treatment for 12 weeks at a standard dose (Remifemin, 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 81 publications
1
13
0
3
Order By: Relevance
“…Similarities exist between hot flashes experienced as a result of going through menopause or opiate withdrawal (46), which is why opiate-dependent animal models have been used to evaluate hot flashes in vivo (47). It has been reported that black cohosh extracts behave as competitive ligands and partial agonists for opiate receptors (44, 48) similar to serotonin receptors (14). A competitive binding assay using a CHO cell line stably transfected with human μ opioid receptors and the same clinical extract used in this study gave an IC 50 of 170 μg/mL (44) compared to 55 μg/mL for the 5-HT 7 receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Similarities exist between hot flashes experienced as a result of going through menopause or opiate withdrawal (46), which is why opiate-dependent animal models have been used to evaluate hot flashes in vivo (47). It has been reported that black cohosh extracts behave as competitive ligands and partial agonists for opiate receptors (44, 48) similar to serotonin receptors (14). A competitive binding assay using a CHO cell line stably transfected with human μ opioid receptors and the same clinical extract used in this study gave an IC 50 of 170 μg/mL (44) compared to 55 μg/mL for the 5-HT 7 receptor.…”
Section: Resultsmentioning
confidence: 99%
“…BCE appears to reduce luteinizing hormone secretion in ovariectomized rats but not in perimenopausal women (Chung et al 2007; Jacobson et al 2001; Jarry and Harnischfeger 1985; Nappi et al 2005; Rachon et al 2008; Reame et al 2008; Seidlova-Wuttke et al 2003); demonstrations of estrogenic/anti-estrogenic activity of black cohosh are inconclusive (Jarry and Harnischfeger 1985; Jarry et al 2003). However, neurotransmitter activities that can modify activity of the hypothalamic-pituitary-gonadal (HPG) axis at the CNS level (reviewed by Rivier and Rivest 1991), including dopaminergic, serotonergic, and opioid activity, have been observed in vitro (Jarry et al 2003; Powell et al 2008; Rhyu et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized that AR activating the neurotransmitter-based effects [2427], rather than the estrogen activity [28, 29], is an important mechanism for alleviating menopausal symptoms, such as hot flashes and night sweats. Numerous studies have also confirmed that AR does not have a stimulating effect on the levels of blood estrogen and progestin or estrogen target organs such as the uterus, ovaries, breast, and blood vessels [9, 22, 30].…”
Section: Discussionmentioning
confidence: 99%